Comparison of Port Security Switch Layer 2 MAC Address Dynamic With MAC Address Static Sticky - Tommi Alfian Armawan Sandi; Firmansyah, Firmansyah; Dewi, Sari; Pratama, Eka Kusuma; Astuti, Rachmawati Darma (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2022)
Security and stability in a network service is a top priority for a network administrator. The slightest security vulnerability can make a very big threat in the stability of network services. The rise of cybercrime that intercepts access to a network service by performing ARP spoofing to imitate a client who has the right to access the network, with this happening it can be detrimental and disrupt network services. The application of MAC Address filtering to access network services is able to minimize the occurrence of cybercrime in the network. The filtering technique used is by registering the MAC address of each network service user who will connect to the network. This technique is able to recap the MAC Address on each device in the MAC Address table and is able to block access to clients whose MAC addresses are not registered. The test results obtained for the comparison of MAC Address filtering security using Dynamic with sticky MAC addresses are that the implementation of port security static sticky is considered better than the implementation of dynamic port security, where if there is a new client trying to access the network and the client's mac address is not registered then the client absolutely does not get access to network services.